Molecular determinism of specific anosmia to 2‐bromo‐4‐methylphenol. (23rd December 2016) - Tempere, Sophie; Schaaper, Marie‐Hélène; Lytra, Georgia; Barbe, Jean‐Christophe; Riquier, Laurent; Marchand, Stephanie; de Revel, Gilles; Sicard, Gilles
Abstract: Several studies have revealed considerable variations in human chemosensory capacities. Considerable interindividual differences in sensitivity to various odorants and specific hyposmias are well known. Many chemical studies have focused on elucidating structure‐odour relationships on the basis of detection threshold measurements. The basic idea of quantitative structure‐activity relationship studies is that a molecule's structure provides information about its biological activity. In a recent sensory assay of 2‐bromo‐4‐methylphenol, Barbe et al . (2014) highlighted a noticeable bimodal distribution of individual sensitivity with large interindividual differences. The aim of the present study was to investigate the link between the chemical structure of 2‐bromo‐4‐methylphenol and this bimodal distribution. The olfactory phenotypes for a selection of six structurally related halogenated compounds were compared using detection thresholds determination. This study revealed that specific anosmia for 2‐bromo‐4‐methylphenol was apparently linked to the halogenated substitution position. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Noticeable bimodal distribution of individual sensitivity with large interindividual differences for the 2‐bromo‐4‐methylphenol. Specific anosmia for 2‐bromo‐4‐methylphenol was apparently linked to the halogenated substitution position.